NTELLECTUAL CAPITAL REALIZATION PROCESS (ICRP), SEBUAH UPAYA MEMETAKAN DAN MEMBENTUK PERSEDIAAN INTELLECTUAL CAPITAL BAGI PERUSAHAAN - Ivada, Elvia; Bayu Bawono, Andy Dwi (Benefit, 2006)
Although Intellectual Capital has become widely accepted as part of the most important assets foran organization, it is still confusing even to recognize it, according to its characteristic that it iscommonly hidden. It is not visible just like traditional assets are, and largely absent from the financialstatement. Trough the Intellectual Capital Realization Process, organizations can map and create aninventory of their IC, so they can use it as a competitive advantage that will bring wealth to theorganization. ICRP is consistent with Resource-Based View (RBV) of the firm that suggests anorganization analysis of its internal resources drives its strategic direction.